2008
DOI: 10.1002/uog.6111
|View full text |Cite
|
Sign up to set email alerts
|

Weight estimation by three‐dimensional ultrasound imaging in the small fetus

Abstract: Objectives To improve birth weight estimation in fetuses weighing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 35 publications
0
27
0
3
Order By: Relevance
“…This might be an indication that the normal assumption by the linear model is not completely unrealistic. The smaller interval widths that can be seen for the linear model are most likely due to the variance estimate in this case ignoring the model choice process that was performed prior to the final model fit by Schild et al (2008). The conditional transformation model takes this variability into account.…”
Section: Birth Weight Predictionmentioning
confidence: 99%
“…This might be an indication that the normal assumption by the linear model is not completely unrealistic. The smaller interval widths that can be seen for the linear model are most likely due to the variance estimate in this case ignoring the model choice process that was performed prior to the final model fit by Schild et al (2008). The conditional transformation model takes this variability into account.…”
Section: Birth Weight Predictionmentioning
confidence: 99%
“…Há mais de duas décadas, já se demonstrava a importância das partes moles, analisada de forma indireta pelo volume de membros fetais, aferido por meio da US2D, como parâmetro de avaliação do crescimento e estado nutricional do feto 18 . Percebe-se que diversas fórmulas já utilizam o volume de membros calculado por meio da US3D (associados ou não a parâmetros bidimensionais) para predição de peso fetal [14][15][16][26][27][28] . Entretanto, nenhuma foi desenvolvida com base na população brasileira.…”
Section: Discussionunclassified
“…Outros pesquisadores optaram por intervalos que variavam de quatro 30 a sete dias 10,17,26,27 . O intervalo médio entre a realização do exame e o parto obtido neste estudo foi de 10,6 horas.…”
Section: Discussionunclassified
“…The authors also assessed the accuracy of this new model in predicting birth weight in 100 singleton pregnancies with delivery estimated to occur within 4 d. Lee et al (2001) reported that a formula based on abdominal circumference and fractional thigh volume was more accurate (within 5% of actual weight) in predicting birth weight than the approach proposed by Hadlock et al (1985). Schild et al (2008) used both 2-DUS and 3-DUS measurements to predict birth weight in fetuses #1600 g in 150 singleton pregnancies with delivery expected to occur within 7 d. The organs evaluated by 3-DUS were the thigh and abdomen, as measured in the multiplanar mode. The model based on biparietal diameter, head circumference, abdominal circumference, femur length and thigh and abdomen volumes proved to be superior to the approach based solely on 2-DUS measurements with biparietal diameter, head circumference, abdominal circumference and femur length as previously described (Campbell and Wilkin 1975;Salomon et al 2011).…”
Section: -Dus In Assessment Of Fetal Organ Volume and Estimation Of mentioning
confidence: 99%